Meningitis in South African adults : an evaluation of prognostic indicators, impact of HIV-infection, and diagnostic dilemmas - Van der Meyden, C.H. (University of Pretoria, 2013)
Thesis (MD (Neurology))--University of Pretoria, 2005.